Neurobehavioral morbidity of pediatric mild sleep-disordered breathing and obstructive sleep apnea. Issue 5 (12th February 2022) - Yu, Phoebe K; Radcliffe, Jerilynn; Gerry Taylor, H; Amin, Raouf S; Baldassari, Cristina M; Boswick, Thomas; Chervin, Ronald D; Elden, Lisa M; Furth, Susan L; Garetz, Susan L; George, Alisha; Ishman, Stacey L; et al.
Abstract: Study Objectives: Obstructive sleep apnea is associated with neurobehavioral dysfunction, but the relationship between disease severity as measured by the apnea-hypopnea index and neurobehavioral morbidity is unclear. The objective of our study is to compare the neurobehavioral morbidity of mild sleep-disordered breathing versus obstructive sleep apnea. Methods: Children 3–12 years old recruited for mild sleep-disordered breathing (snoring with obstructive apnea-hypopnea index < 3) into the Pediatric Adenotonsillectomy Trial for Snoring were compared to children 5–9 years old recruited for obstructive sleep apnea (obstructive apnea-hypopnea 2–30) into the Childhood Adenotonsillectomy Trial. Baseline demographic, polysomnographic, and neurobehavioral outcomes were compared using univariable and multivariable analysis. Results: The sample included 453 participants with obstructive sleep apnea (median obstructive apnea-hypopnea index 5.7) and 459 participants with mild sleep-disordered breathing (median obstructive apnea-hypopnea index 0.5). By polysomnography, participants with obstructive sleep apnea had poorer sleep efficiency and more arousals. Children with mild sleep-disordered breathing had more abnormal executive function scores (adjusted odds ratio 1.96, 95% CI 1.30–2.94) compared to children with obstructive sleep apnea. There were also elevated Conners scores for inattention (adjusted odds ratio 3.16, CI 1.98–5.02) and hyperactivity (adjusted odds ratio 2.82, CI 1.83–4.34) in children recruited for mild sleep-disordered breathing. Conclusions: Abnormal executive function, inattention, and hyperactivity were more common in symptomatic children recruited into a trial for mild sleep-disordered breathing compared to children recruited into a trial for obstructive sleep apnea. Young, snoring children with only minimally elevated apnea-hypopnea levels may still be at risk for deficits in executive function and attention. Trial Registration: Pediatric Adenotonsillectomy for Snoring (PATS), NCT02562040; Childhood Adenotonsillectomy Trial (CHAT), NCT00560859